Varieties of business models for post-consumer recycling in China. (1st January 2018) - Tong, Xin; Tao, Dongyan; Lifset, Reid
Abstract: The effort to build an EPR system for waste electrical and electronic equipment (WEEE) in China has created unexpected niches for innovation in business models for post-consumer recycling of e-waste as well as other recyclables in recent years. This study used action research to evaluate the performance of emerging business models for post-consumer recycling in urban China in recent years. We identified three categories of emerging models: (1) community-based programs targeting the garbage sorting behavior of consumers for all household waste, (2) reverse logistic systems with automatic vending machines attached to traditional commercial chains, and (3) pure internet solutions to bridge the transactions between the consumers and recyclers. All these business models share the common characteristic that they use internet technology, which is aggressively promoted in China as "Internet +" by both government policies and venture capital investment. The various business models serve as the link between the firm and the system level and reflect the diverse possibilities for the future evolution of the recycling system in China. We developed a qualitative evaluation framework with five elements including convenience for consumers, traceability for producers, profitability for recyclers, hybridity for collection, and reliability of the information used by the public to address the various values pursued by different actors involved in the recycling chains. The results reveal the dilemmas facing each business model in balancing among all the elements and highlight the governance challenge of integrating the EPR scheme with the municipal waste management system. Highlights: The government recycling funding for waste electrical and electronic equipment (WEEE) in China has created unexpected niches for innovation in business models for post-consumer recycling. Three emerging business models for post-consumer recycling with IT solutions are identified: community-based recycling programs, automatic reverse vending machine chains, and pure Internet platform. An evaluation framework is presented with five elements, convenience for consumers, traceability for producers, profitability for recyclers, hybridity for collection, and reliability for public, to address the various values pursued by different actors involved in the recycling chains.